The associations of breastfeeding and postnatal experiences with postpartum depression among mothers of hospitalized infants in tertiary hospitals - Mohd Shukri, Nurul Husna; Senjaya, Olivia; Zainudin, Zurina; Mohamed, Maslina; Syed Abdullah, Farah Inaz (Cureus, 2022)
Background: Postpartum depression has been linked to undesirable outcomes for mother-infant dyads, interfering with childcare and breastfeeding practices. This study aimed to determine the prevalence of depressive symptoms among mothers during the postpartum period and its association with breastfeeding and postpartum experiences. Methodology: This cross-sectional study involved mothers of hospitalized infants (n = 219) at two tertiary hospitals in Klang Valley, Malaysia. Mothers were screened for postpartum depression using the Edinburgh Postnatal Depression Scale with a cut-off of ≥12 for positive screening for depression. Mothers were asked to complete questionnaires on breastfeeding experience, which included breastfeeding self-efficacy and challenges. The questionnaires also collected information on postnatal experiences, including birth outcomes, anxiety and stress levels, and social support. Multiple linear regression was used to ascertain the association of postpartum depression levels with breastfeeding and postnatal experiences. Results: Overall, 30% of mothers in this study screened positive for depression. Based on multiple linear regression, a higher score of postpartum depression was significantly associated with unpleasant breastfeeding and postnatal experiences reflected by increased scores of anxiety and stress, lower infant birth weight, increased breastfeeding problems, and lower level of social support (p < 0.005). Conclusions: Maternal emotions, birth outcomes, breastfeeding issues, and social support were associated with postpartum depression. Efforts should be made to increase maternal support, and screening for maternal depression during infant hospital stays should be encouraged.